Extracellular matrix containing nanocomposite bone graft in periodontal regeneration – A randomized controlled clinical and radiographic evaluation - Abhinav Prakash Deshpande; Mala Dixit Baburaj; Lashika Vasant Tambe; Upendra Prasad (Journal of Indian Society of Periodontology, 2021)
Background: The study aims to evaluate the effect of adding extracellular matrix (ECM) component – natural collagen to nanocrystalline hydroxyapatite (nHA) bone graft in the treatment of intrabony defect in chronic periodontitis patients. Materials and Methods: Forty chronic periodontitis patients having at least one intrabony defect were treated surgically by open flap debridement and the defect grafted (Group A: 20 sites grafted with nHA with natural collagen and Group B: 20 sites grafted with nHA). Plaque index, gingival index, probing pocket depth (PPD), clinical attachment level (CAL), and radiographic defect depth (RDD) were evaluated. Results: The mean PPD reduced from 7.6 ± 0.88 at baseline to 4.45 ± 0.69 and 2.60 ± 0.6 at 3 and 6 months, respectively, in Group A. In Group B, the mean PPD reduced from 7.5 ± 0.89 at baseline to 4.95 ± 0.60 and 2.65 ± 0.59 at 3 and 6 months, respectively. The mean CAL reduced from 7.75 ± 0.85 at baseline to 5.05 ± 0.76 and 3.6 ± 0.68 at 3 and 6 months, respectively, in Group A. In Group B, the mean CAL reduced from 7.70 ± 0.86 at baseline to 5.8 ± 0.7 and 3.75 ± 0.64 at 3 and 6 months, respectively. The mean RDD reduced from 8.13 ± 0.78 and 8.12 ± 0.83 at baseline to 4.27 ± 0.66 and 3.94 ± 0.5 after 6 months in Groups A and B, respectively. After 3 months, a statistically significant reduction in mean PPD and CAL values was noted in Group A while the results were comparable after 6 months. Conclusion: The effectiveness of nHA composite during initial healing phase (3 months) can be attributed to the presence of ECM-collagen in bone graft matrix.